CHARACTERIZATION AND GENETIC IMPROVEMENT OF ASPARAGUS RACEMOSUS (WILLD.) : AN IMPORTANT MEDICINAL PLANT - Parveen, -; Kumar, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Asparagus racemosus (Willd.) is an important medicinal plant known as Shatawari, means who possesses more than hundred husbands. It is the main Ayurvedic medicinal tonic especially for the female, as is Withania somnifera for the male. It is commonly mentioned as a rasayana in the Ayurveda, the drug which promotes general well being of an individual by increasing cellular vitality or resistance. A. racemosus reached endangered in nature due to its over-exploitation, as the fleshy roots of the species contain saponin having therapeutic value. It is one of the 32 plant species identified as priority species for cultivation and conservation by the National Medicinal Plant Board (NMPB), India. Owing to increased demand, the species has attracted the attention for its genetic improvement, conservation and cultivation. Accordingly, germplasm has been collected from different geographical regions of India, and a scientific field trial of 20 sources has been established at the Forest Research Institute, Dehradun to evaluate comparative performance of economic traits, stability and adaptability. The significant genetic variations for different morphological traits including plant type, maturity period, growth and yield characters and size / shape of tubers was determined and the potential genotypes for higher productivity have been identified. The morphological traits identified at nursery stage could be utilized for screening of plants with maximum tubers production at early age. As A. racemosus is a cross pollinated species, attempts have also been made for production of F1 hybrids. The programme is useful for genetic conservation for realization of future breeding strategies.